Jogo Tonggo : Solidaritas Masyarakat di Era Pandemi Covid-19 - Probosiwi, Ratih; Putri, Afrinia Lisditya (Puslitbangkesos Kementerian Sosial RI, 2021)
This paper examined the Jogo Tonggo policy issued by the Central Java Provincial Government in the face of the Covid-19 pandemic. Methodology: This research is a qualitative descriptive, data were collected by in-depth interviews with respondents who were selected by snowball sampling. The research was conducted in Purworejo Regency. Result: The Covid-19 pandemic changed the pattern of relations between communities through the local (village) self-contained quarantine that was enforced in villages. Several village-level social activities were canceled to avoid crowds. Jogo tonggo begins with the provision of PPE and disinfectant equipment. Community solidarity with neighbors is established as usual, even better, for example helping neighbors who must self-quarantine. The form of solidarity that is carried out is by taking turns providing foodstuffs for 14 days of quarantine with a varied menu managed by the PKK or Dasawisma group. The community also routinely works together in spraying disinfectants, guarding the entrance portal which is managed in rotation. Recommendation: This movement needs to be continuously advocated so that people who are getting fed up with pandemic conditions remain vigilant and do not ignore health protocols. It is also necessary to think about a stimulus for villages to assist with foodstuffs, medical devices and internet quota packages for school children.Â Keywords:Â Social solidarity; neighborhood; helping each other